2018
DOI: 10.1097/ede.0000000000000868
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Road Traffic Noise and Body Mass Index Trajectories from Birth to 8 Years

Abstract: Background:Being overweight constitutes a health risk, and the proportion of overweight and obese children is increasing. It has been argued that road traffic noise could be linked to adiposity through its influence on sleep and stress. Few studies, to our knowledge, have investigated whether noise and adiposity are associated. Most of them were on adults, and we are not aware of any longitudinal study using repeated measures.Objectives:The present longitudinal study investigated whether road traffic noise exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 50 publications
1
23
1
Order By: Relevance
“…The results of the present study are in line with most previous studies, which rather consistently found road traffic noise to be associated with markers of adiposity 2–4 9–13. However, our study population of women during and after pregnancy (mean age of 30 years) differs from populations used in previous studies, which focused on either children12 13 or older populations 2–4 9–11.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the present study are in line with most previous studies, which rather consistently found road traffic noise to be associated with markers of adiposity 2–4 9–13. However, our study population of women during and after pregnancy (mean age of 30 years) differs from populations used in previous studies, which focused on either children12 13 or older populations 2–4 9–11.…”
Section: Discussionsupporting
confidence: 91%
“…Studies of both cross-sectional and longitudinal designs have rather consistently found transportation noise to increase waist circumference and obesity among adults, whereas results for body mass index (BMI) are less consistent 2–4 9–11. Two recent studies have moreover indicated that traffic noise may affect adiposity in children 12 13. Exposure to transportation noise is believed harmful through a stress reaction, with activation of the hypothalamic–pituitary–adrenocortical axis, leading to a rise in stress hormones, vascular dysfunction and metabolic abnormalities such as impaired glucose tolerance 14–18.…”
Section: Introductionmentioning
confidence: 99%
“…1. Full text review yielded 24 publications for inclusion into the systematic review and meta-analyses [35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]. The list of excluded studies with reasons for exclusion is available in SI 5.…”
Section: Eligible Studies and Characteristicsmentioning
confidence: 99%
“…We performed two separate meta-analyses for BMI and body fat datasets. Table 1 altogether with SI 6 illustrate the characteristics of the 19 included studies [35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,53,55,56,58]. Thirteen studies included a relatively similar amount of males and females.…”
Section: Figmentioning
confidence: 99%
“…It has been discussed that the living environment including noise exposure and an unsecure living environment influence weight development in adults [ 27 29 ]. Since data on the effects of such stressors on children is sparse [ 30 ] we included not only the socioeconomic status of the study participants, but also factors characterizing their living environment such as traffic or residential noise in our analysis.…”
Section: Introductionmentioning
confidence: 99%